Immune remodeling and atrial fibrillation - Yao, Yajun; Yang, Mei; Liu, Dishiwen; Zhao, Qingyan (Frontiers in Physiology, 2022)
Atrial fibrillation (AF) is a highly prevalent arrhythmia that causes high morbidity and mortality. However, the underlying mechanism of AF has not been fully elucidated. Recent research has suggested that, during AF, the immune system changes considerably and interacts with the environment and cells involved in the initiation and maintenance of AF. This may provide a new direction for research and therapeutic strategies for AF. In this review, we elaborate the concept of immune remodeling based on available data in AF. Then, we highlight the complex relationships between immune remodeling and atrial electrical, structural and neural remodeling while also pointing out some research gaps in these field. Finally, we discuss several potential immunomodulatory treatments against AF. Although the heterogeneity of existing evidence makes it ambiguous to extrapolate immunomodulatory treatments against AF into clinical practice, immune remodeling is still an evolving concept in AF pathophysiology and further studies within this field are likely to provide effective therapies for AF.